PELATIHAN DAN PERTUNJUKAN DRUMBAND BAGI SISWA SMP NEGERI 30 KABUPATEN MUARO JAMBI DALAM MENINGKATKAN KETERAMPILAN BERMUSIK - Indra Gunawan; Mahdi Bahar; Ikhsan Satria Irianto; Riswani (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The Independent Curriculum in elementary to high schools (SD to SMA) is a challenge for schools to improve their ability in managing both learning and administration, so that what is aspired to in the mandate of the Constitution which reads "to educate the life of the nation" is something that is essential. Something that is quite urgent is the learning objectives, one of which is to improve cognition for students, which is the basis for this community service program, namely improving musical skills with a drumband training and performance program at SMPN 30 Muaro Jmabi. The skills program in the independent learning curriculum is strongly encouraged by being a leading government program (Ministry of Education and Culture) so that students can create something that fosters independence in determining and choosing the direction of life (future). The purpose of this community service program is that in addition to increasing interest and talent, it also provides space for creativity for students in carrying out music learning activities through extracurricular activities as intended by the independent curriculum. The community service program is a government program that is assigned to educators (Lecturers) in carrying out the Tri Dharma of Higher Education. For that, of course there are scientific measurements called activity outputs, in this case the team will target outputs in the form of (1) National Seminar Proceedings. (2) Scientific Journals. (3) Publications on Electronic Media. (4) Activity Documentation Videos.